The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jpowsour.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of capacitive performances of symmetric carbon/carbon supercapacitors by addition of nanostructured polypyrrole powder

Abstract: International audienceA nanostructured polypyrrole powder was synthesized in a previous work from the oxidation of pyrroleby a nanostructured MnO2 powder used simultaneously as an oxidizing agent and a sacrificial templatein a redox heterogeneous mechanism. In this study, this original PPy powder was used as an activeadditive material with different ratio in carbon/carbon symmetrical supercapacitors whose performanceswere studied by cyclic voltammetry and electrochemical impedance spectroscopy (EIS) using aSwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 48 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…Moreover, they can be functionnalised using different strategies such as covalent grafting of functional groups on their monomers, electrochemical doping, or insertion of nano-objects (nanoparticles, enzymes, …) during the synthesis step. All the abovementioned properties of ECPs are electrochemically tunable, which justifies that ECPs are widely involved in a large number of applications, among which one can cite, in a non-exhaustive list, supercapacitors [3][4][5][6][7],…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they can be functionnalised using different strategies such as covalent grafting of functional groups on their monomers, electrochemical doping, or insertion of nano-objects (nanoparticles, enzymes, …) during the synthesis step. All the abovementioned properties of ECPs are electrochemically tunable, which justifies that ECPs are widely involved in a large number of applications, among which one can cite, in a non-exhaustive list, supercapacitors [3][4][5][6][7],…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Polypyrrole (PPy) has attracted wide attention due to its advantages of simple synthesis, environmental protection, low cost, and nontoxicity. [21][22][23][24] In addition, the transition metal tungsten oxide (WO 3 ) is considered a promising negative electrode material due to its abundant resources, various valence states, and electrochemical activity at negative potential. [25][26][27][28] Many studies have reported the application of a PPy and WO 3 composites in gas-sensing and electrochromic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Some drawbacks of such materials can be corrected by the addition of carbon materials. In order to overcome the issues associated with poor cyclability of PPy (which occur mostly due to its volume changes during faradaic processes such as redox reactions) and improve the mechanical properties, the allotropes of carbon with nanoscale diameter, that is, nanotubes or graphene are mainly applied . Many approaches have been developed to overcome problems associated with the homogeneous dispersion of carbon nanostructures in composite materials.…”
Section: Introductionmentioning
confidence: 99%